Enhanced uniformity in electrical and optical properties of ITO thin films using a wide thermal annealing system. (1st June 2018) - Seong, Sejong; Jung, Yong Chan; Lee, Taehoon; Park, In-Sung; Ahn, Jinho
Abstract: We investigated the effects of thermal treatment using a wide thermal annealing (w-TA) system on the structural, electrical, and optical properties of indium tin oxide (ITO) thin films deposited by radio-frequency magnetron sputtering at room temperature. The w-TA system was designed to enhance the uniformities of the electrical and optical properties of thin films in a large-scale 8G display substrate. The ITO films were annealed at 350 °C and 450 °C in a planar w-TA chamber. The X-ray diffraction analysis showed crystallization of ITO films along the 〈111〉 direction after the annealing process and an increase in their crystallite size with process temperature. The uniform characteristics of the electrical resistance and optical transmittance of ITO films are suitable for wide transparent electrodes, being the major advantage of the w-TA system. The sheet resistance (Rs ) of the ITO thin films was lower, down to 18 Ω/□, and the variation of the Rs value was also narrowed down, which is measured by Rs at diverse points, after the w-TA process. The carrier concentration and mobility of the ITO films improved with an increase in annealing temperatures. The annealed ITO films exhibited both improved transmittance and better uniformity in the visible light region on a large 8G substrate. The band gap energy and carrier concentration of the ITO films increased after thermal annealing, as suggested by both the blue shift of the refractive index and the extinction coefficient values.